A two-stage stochastic model for location planning of temporary medical centers for disaster response. (April 2020) - Oksuz, Mehmet Kursat; Satoglu, Sule Itir
Abstract: Devastating effects of disasters and global crises on people increase the importance of humanitarian logistics studies for pre and post-disaster stages. Location planning of Temporary Medical Centers/field hospitals is one of the most important problems for disaster response. We aimed to determine the location and number of temporary medical centers in case of disasters by considering the locations of the existing hospitals, casualty classification (triage), capacities of medical centers and possibilities of damage to the roads and hospitals. Besides, we aimed to assign different casualty classes to these medical centers for emergency medical response by considering the distances between disaster areas and medical centers. For this purpose, a two-stage stochastic programming model was developed. The proposed model finds an optimal TMC location solution while minimizing the total setup cost of the TMCs and the expected total transportation cost by considering casualty types, demand, possibilities of damage to the roads and hospitals, and distance between the disaster areas and the medical centers. In the model, α-reliability constraints for the expected number of unassigned casualties were also used. Besides, the model was reformulated without triage, in order to understand the impact of casualty classification on the solution of the problem. We performed a real case study for the district of Kartal expected to be widely damaged in the possible Istanbul earthquake, and a sensitivity analysis was made. The analysis of the results offer some managerial insights associated with the number of temporary medical centers' needed, their locations, and additional hospital capacity requirements. Highlights: A two-stage stochastic programming model is proposed for location planning of Temporary Medical Centers. Total setup cost of TMCs and expected total casualty transportation cost are minimized. Triage, α-reliability constraints and probability of damage to the hospitals and roads are considered. A case study was conducted for earthquake scenarios of Istanbul's Kartal district. Triage helps prevent significant differences of unassigned casualty percentages among demand points.